Appetite for Destruction: A Psychometric Examination and Prevalence Estimation of Destructive Leadership in Sweden - Lundmark, Robert; Stenling, Andreas; von Thiele Schwarz, Ulrica; Tafvelin, Susanne (Frontiers in Psychology, 2021)
There is a growing awareness that destructive leadership has a significant negative impact on employee outcomes. However, little is known about the content and dimensionality of this multidimensional concept, and there are few reliable measures available for organizations and researchers to evaluate these behaviors. Based on a representative sample (N = 1132), the aim of this study is threefold: first, to examine the factor structure and validity of an easy-to-use multidimensional destructive leadership measure (Destrudo-L) in the general Swedish work context; second, to identify destructive leadership profiles using latent profile analysis (LPA), and determine in what way they are related to employee outcomes; third, to examine the prevalence of destructive leadership using population weights to estimate responses of a population total in the Swedish workforce (N = 3100282). Our analysis supported the structural validity of Destrudo-L, reflecting both a global factor and specific subdimensions. We identified seven unique destructive leadership profiles along a passive and active continuum of destructive leadership behaviors, with the active showing a less favorable relation to employee outcomes. Finally, we found that a substantial proportion of the Swedish workforce report being exposed to destructive leadership (36.4 – 43.5 %, depending on method used). Active destructive leadership was more common in the public sector and passive destructive leadership in the private. Given the potentially severe effects and the commonness of these behaviors, we argue that organizations should work actively with strategies to identify and intervene, to prevent and to handle the manifestation of these harmful behaviors.